2019
DOI: 10.1111/his.13941
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical spectrum of dermal hyperneury: report of nine new cases and a review of the literature

Abstract: Aims Dermal hyperneury is defined as the hypertrophy of small nerves in the dermis. It has been described in a variety of settings. We present a series of nine new cases with a distinctive clinical presentation and review the existing literature. The aim of the study was to summarise the clinical, histopathological and immunohistochemical findings in a case series of dermal hyperneury with unique clinical presentation. Methods and results Nine cases were identified from the referral practice of one of the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The neuropathic chronic pain in post-acute COVID-19 patients has been recently described by Ieremia et al, who reported loss of dermal neurosensory fibers in nine patients [ 28 ]. Compared to our findings of hypertrophy, fiber loss and inflammation could be related to a later phase of the disease, in which chronic inflammation leads to atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathic chronic pain in post-acute COVID-19 patients has been recently described by Ieremia et al, who reported loss of dermal neurosensory fibers in nine patients [ 28 ]. Compared to our findings of hypertrophy, fiber loss and inflammation could be related to a later phase of the disease, in which chronic inflammation leads to atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In two cases the neuro-vascular complexes showed a glomeruloid appearence. The overall apperance was that of dermal hyperneury, a condition known to occur in the context of different syndromes (e.g., MEN2a, MEN2b, PTEN hamartoma tumor syndrome and NF2) or in association with skin acquired disorders (e.g., Nodular Prurigo and Notalgia Paresthetica) 2 . SARS-CoV-2 could be involved in “burning skin” through a malfunction of the myelinated A-delta and unmyelinated C primary afferent neuronal fibres, due to the activation of the immune-mediated inflammatory response and host-related factors.…”
mentioning
confidence: 99%
“…In two cases the neuro-vascular complexes showed a glomeruloid appearence. The overall apperance was that of dermal hyperneury, a condition known to occur in the context of different syndromes (e.g., MEN2a, MEN2b, PTEN hamartoma tumor syndrome and NF2) or in association with skin acquired disorders (e.g., Nodular Prurigo and Notalgia Paresthetica) 2 .…”
mentioning
confidence: 99%